The study of reactivity state of Schneiderian membrane under some forms of stomatogenic maxillary sinusitis - Варжапетян, Сурен Диасович (ScienceRise: Medical Science, 2016)
The one of causes of the high prevalence rates of the chronic maxillary sinusitis is an absence of differentiated approach to the treatment of the different forms of this pathology. The spread of infection on the mucous tunic of maxillary sinus takes place already after extraction of tooth with gangrenous pulp as a result of suppuration of the maxilla root cyst, at osteomyelitis of alveolar process, after operations of sinus-lifting at implantation of maxillary teeth. Standardization of treatment of inflammatory pathological states in maxillary sinus that have different causes and mechanisms of development leads to the temporal extinction of expressed clinical symptoms only, favoring the chronization of disease. Aim of research: To study morphological changes of Schneiderian membrane at odontogenic and iatrogenic (traumatic form) maxillary sinusitis of stomatogenic origin. Material and methods There were studied intraoperational biopsy materials of 14 (19,7 %) patients with odontogenic maxillary sinusitis (control group) and 57 (80,3 %) patients with traumatic form of iatrogenic maxillary sinusitis (main group). For the survey microscopy histological sections were colored with hematoxylin and eosin, where the height of mucous tunic epithelium, absolute area of leuko-lymphocytic and hemorrhagic infiltrates were defined, the state of vessels of microcirculatory channel was assessed. For analysis of the process of fiber-creation in studied samples, the sections were colored with Weigert hematoxylin according to Van Gieson. For qualitative and quantitative study of cells distribution in mucous tunic of maxillary sinus the morphometric net of S.B. Stephanov was used. Manasse pathomorphological classification was used for differentiation of the revealed changes in mucous tunic. For revelation of the natural killer cells, the sections were colored with alcian blue (critical concentration of magnesium chloride 0,6 Mol) with additional coloration of kernels with hematocylin. The reactions with СD 8, CD 56, CD 68, CD 138, CD 43 monoclonal antibodies were carried out. Streptavidin-biotin system of visualization of LSAB2 antibodies (peroxidate mark + benzidine) (LabVision, USA) was used. The number of CD 8+, CD 68+ cells in sight was counted. All prescriptions of solutions were taken from instructions. Photodocumentation was carried out using Axiolab binocular microscope, Axiocam digital camera with 8 megapixel matrix, personal computer, connected with digital camera by interface, video cable and «AxioVision 4.8» software. Statistical processing of the received results was carried out using tables of R.B. Strelkov, by accelerated method of quantitative comparison of morphological preparations. The reliability of the received results were assessed according to the method of Student-Fisher for reliability level no less than 95 %,that is conventional for biological and medical studies (р<0,05). Results of research. Odontogenic maxillary sinusitis is characterized with diffuse and focal mainly macrophagic-lymphocytic and hemorrhagic infiltration of the proper plate of the mucous tunic (35,7±12,8 %, р>0,05); fibrosis of the proper plate of the mucous tunic of maxillary sinus, in several cases more expressed proliferation of collagenous fibers of the proper plate (21,4±10,9 %, р>0,05); expressed edema of the proper plate tissue with effusion in extracellular matrix (14,3±9,3 %, р>0,05); cysts (7,2 %, р>0,05). CD 8+ (8,48±0,25 %), were found in infiltrate, CD 68+ macrophages prevail (21,5±0,4 %), CD56+ cytotoxic lymphocytes (singular), CD 43+ complexes, CD 138+ cells (in insignificant number). In Schneiderian membrane epithelium were revealed desquamation (64,3±12,8 %), necrosis (57,1±13,2 %), focal planocellular metaplasia (42,9±13,2 %), vacuole dystrophy of epithelial cells (42,9±13,2 %), intraepithelial lymphocytic infiltration (35,7±10,2 %). In average epithelium height is 44,6±1,5 mcm. Traumatic form of iatrogenic maxillary sinusitis is characterized with expressed diffuse and focal mainly macrophagic-lymphocytic and hemorrhagic infiltration of the proper plate of the mucous tunic (36,8±6,3 %, р<0,05); fibrosis of the proper plate of the mucous tunic of maxillary sinus, uneven thickening of basal epithelium membrane (31,6±6,1 %, р<0,05); expressed proliferation of collagenous fibers of the proper plate, expressed edema of the proper plate and polyps (10,5±4,0 %, р<0,05). Cysts were not observed. CD8+ in infiltrate (perivascular), CD 68+ (15,53±0,18 %) macrophages, CD56+ cytotoxic lymphocytes (16,7±4,9 %), CD 43+ (are situated diffusely), CD 138+ prevailing cells (100 %). In Schneiderian membrane epithelium were revealed necrosis (57,9±6,5 %), metaplasia (47,4±6,6 %), loss of ciliary cover (63,2±6,3 %), intraepithelial lymphocytic infiltration (42,1±6,5 %). In average epithelium height is 62,9±2,28 mcm. Conclusions. Patients with odontogenic injury of sinus are characterized with expressed vascular reaction, aseptic inflammation. The moderate proliferation of collagenous fibers, especially around vessels, glands, along basal epithelium membrane, disorders of epithelium lane, necrosis nidi, desquamation, planocellular metaplasia. The loss of ciliary cover on the background of necrosis, planocellular metaplasia and intraepithelial lymphocytic infiltration prevail in patients with traumatic form of iatrogenic maxillary sinusitis of stomatogenic origin. Restoration of epithelium cover that provides mucous-ciliary clearance is possible because of absence of brightly expressed fibrosis of the proper plate of mucous tunic